Role of Pannexin-1 hemichannels and purinergic receptors in the pathogenesis of human diseases - Velasquez, Stephani; Eugenin, Eliseo A. (Frontiers in Physiology, 2014)
In the last decade several groups have determined the key role of hemichannels formed by pannexins or connexins, extracellular ATP and purinergic receptors in physiological and pathological conditions. Our work and the work of others, indicate that the opening of Pannexin-1 hemichannels and activation of purinergic receptors by extracellular ATP is essential for HIV infection, cellular migration, inflammation, atherosclerosis, stroke and apoptosis. Thus, this review discusses the importance of purinergic receptors, Panx-1 hemichannels and extracellular ATP in the pathogenesis of several human diseases and their potential use to design novel therapeutic approaches.